Impacts of COVID-19 on Firms in the Philippines : Results from the Philippines COVID-19 Firm Survey conducted in November 2020 - World Bank (World Bank, Washington, DC, 2021)
The findings are based on the survey of 13,878 firms conducted from November 26 to December 10, 2020, to assess the impacts of COVID-19 on firms. This survey builds on a government survey in April 2020 and the World Bank-government joint survey in July 2020, both of which benefit from a large sample size and present a nationwide representative snapshot of firms in the Philippines. Easing of the community quarantine has led to more businesses reopening (63 percent in November vs. 45 percent in July), but with only a small proportion operating at full capacity (9 percent). While some managers closed businesses in compliance with government regulation (9 percent), others voluntarily closed their businesses (21 percent) despite eased community quarantines. About 7 percent of firms reported to have closed permanently. Reduction in sales has continued for firms. 67 percent of firms reported a reduction in sales between July and November 2020, compared to 88 percent between April and July 2020. The main reason for decreased sales is limited operation (58 percent) and inability of customers to come to establishments (38 percent). Downward adjustments of employment continued in November 2020 (38 percent), albeit at a slower pace than in July 2020 (50 percent). Significant shares of firms also made adjustments on the intensive margin, reducing hours (19 percent) and wages (16 percent). Only 3 percent of firms hired new employees. A large share of firms reported acute liquidity constraints, with reports of not having enough cash and having fallen behind in payments. 66 percent of firms did not have enough cash to pay all costs and payments such as payroll, suppliers, taxes or loan repayment beyond 1 month. Two thirds of firms had adjusted loan repayment terms, and 48 percent of firms were in arrears, with an additional 29 percent expecting to be in arrears by February 2021. Despite firms expressing cautious optimism that sales and employment will increase over the next 3 months, many expect their financial positions to worsen.